The Effects of Personality Types and Demographic Factors on Overconfidence Bias and Decision Making of Investment Types - Benny Budiawan Tjandrasa; Jacqueline Mariae Tjandraningtyas (Master of Management, School of Business and Management, Petra Christian University, 2018)
In financial management theories an investor will act rationally and make a desicion to invest based on the rules in the financial management theory. Nevertheless, in reality the decision making to invest is very often irrational and not in accordance with the financial management theory. This deviation is caused by the bias of investors’ behaviour in making a decision. Investors who only focus on the return of an investment without paying attention to the risks are said to experience overconfidence bias. This research analyses the factors which are considered to influence investors with overconfidence bias in deciding the investment types. The factors are personality type, marital status, income level, work experience, and fields of study that have been taken. This research can contribute to completing the study of financial management, particularly in the investment decision and putting psychological factors in the analysis of financial management